Microstructure and mechanical properties of hot-pressed SiC nanofiber reinforced SiC composites. Issue 11 (1st June 2022) - Yang, Jiahao; Ma, Ruiqi; Zhu, Mingming; Xiong, Yilian; Shi, Jiahui; Li, Xiaohong; Li, Haolin; Chen, Jianjun
Abstract: This study reports on the preparation and mechanical properties of a novel SiCnf /SiC composite. The single crystal SiC nanofiber(SiCnf ) reinforced SiC ceramic matrix composites (CMC) were successfully fabricated by hot pressing the mixture of β -SiC powders, SiCnf and Al–B–C powder. The effects of SiCnf mass fraction as well as the hot-pressing temperature on the microstructure and mechanical properties of SiCnf /SiC CMC were systematically investigated. The results demonstrated that the 15 wt% SiCnf /SiC CMC obtained by hot pressing (HP) at 1850 °C with 30 MPa for 60 min possessed the maximum flexural strength and fracture toughness of 678.2 MPa and 8.33 MPa m 1/2, respectively. The nanofibers pull out, nanofibers bridging and cracks deflection were found by scanning electron microscopy, which are believed can strengthen and toughen the SiCnf /SiC CMC via consuming plenty of the fracture energy. Besides, although the relative density of the prepared SiCnf /SiC CMC further increased with the sintering temperature rose to 1900 °C, the further coarsend composites grains results in the deterioration of the mechanical properties for the obtained composites compared to 1850 °C.